Penentuan Karakterisasi Cerrobend Sebagai â€œWedge Filterâ€ Pada Pesawat Teleterapi 60Co - Azam, Much.; Firdausi, K. Sofjan; Silvani, Sisca (BERKALA FISIKA, 2006)
Wedge filter usually used in cavum nasi ossa maxillaris tumor therapy. And usually it is made of timbal. However, cerrobend as the alternative material is possible and needed too. The material characterization is done through determining the linear absorption coeffisien of cerrobend and the proportion of the thickness of cerrobend to timbal, and as well as comparing the total treatment dose rate of timbal wedge filter with cerrobend wedge filter. Based on the result of the research, it is found that the linear absorption coeffisien value of cerrobend wedge filter with energy of 1.33 MeV is 0.43% cm-1. The average ratio of the thickness of cerrobend to timbal is 1.485 ± 0.002, and the difference of the total treatment dose rate between those two wedge filter is only a little, that is 0.72 cGy/minutes. Keywords : cerrobend, wedge filter and the linear absorption coeffisien